SUSTAINABILITAS HUTAN TANAMAN INDUSTRI SENGON (Albizia falcataria) - Subari, Darni (Kementerian Perindustrian, 2014)
Forest degradation and deforestation caused a decline in the ability of forest resources. Therefore, forest management is more serious and thoughtful in order to sustainable forest development is needed to prevent further damage . The installed capacity of the industrial units in South Kalimantan as a whole ± 2,338,329.70 m3. When yield industrially ± 50 % , it is normally necessary 4,676,594.00 m3 of raw materials, raw materials capable of being supplied by the forest ± 1,394,362.07 m3, so there is a large enough difference shortcomings, namely ± 3 million m3/year, which can be met by developing industrial tree plantation forests especially Sengon (Albizia falcataria). In order to plantation development and manufacture of the plant is directed to the formation of units HTI which is require both of managerial technic and economic aspects, so it should be directed at the development of a model of the units in accordance with the plan. Such models use Faustman models and the process is called sequent harvest (Fauzi, A. 2006). With a management system based on economic principles right (Faustman models with sequent harvest) T (time) for construction timber types Sengon (Albizia falcataria) for 12 years and a lumpsump tax arrangement system and facilitated the policy of the government, then Sengon HTI can provide sustainable benefits.Keywords: HTI, sengon, sequent harvest, lumpsum tax